Composite supersymmetries in low-dimensional systems - Alexandre, J; Mavromatos, N; Sarkar, S (IOP Publishing, 2002)
Starting from a N = 1 scalar supermultiplet in 2+1 dimensions, we demonstrate explicitly the appearance of induced N = 1 vector and scalar supermultiplets of composite operators made out of the fundamental supersymmetric constituents. We discuss an extension to a N = 2 superalgebra with central extension, due to the existence of topological currents in 2+1 dimensions. We comment on the relevance of these results for an effective description of the infrared dynamics of planar high-temperature superconducting models with quasiparticle excitations near nodal points of their Fermi surface.